Feasibility of Detecting Brain Areas Involved in Extreme Breath-Hold Diving - Patrice, Jissendi-Tchofo; Yassin, Jdaoudi; Peter, Germonpré; Danilo, Cialoni; Andrea, Brizzolari; Patrick, Musimu; Costantino, Balestra (Journal of Neurological Research And Therapy, 2021)
A feasibility study explores neuroimaging approaches to identify brain regions engaged during extreme breath‑hold diving. Methods, safety considerations, and preliminary activation patterns are summarized to motivate further controlled studies.
Keywords: breath-hold protocol; fMRI technique; Cerebral Decompression illness